Studi Awal Teknik Perekaman Citra pada Perangkat Medis untuk Efisiensi Distribusi Citra Medis - Bernardinus Sri Widodo; Agatha Mahardika Anugrayuning Jiwatami (SILAMPARI JURNAL PENDIDIKAN ILMU FISIKA, 2023)
Medical imaging is one method that is widely used to provide information about the physical parts of the body for diagnosis and therapy. This research is an initial study to find appropriate technology to record medical imaging results in the form of photos and videos so that they are ready to be distributed to support the telemedicine process. This research was conducted by studying literature on the equipment that might be used for the screen capture process, followed by making a prototype of the tool to be used as FGD material. During the FGD process, discussions were held with radiology specialists and gynecologists, nurses and technicians to find out the impact of this tool. The results show that it is possible to distribute medical images using screen capture techniques. This research is the first step for the development of medical image distribution.